Harnessing the metabolites from the marine sponge Melophlus sarasinorum for the discovery of eco-friendly antifoulants - WALTER BALANSA; RIYANTI RIYANTI; MARIA A. PATRAS; KIRSTEN H. BALANSA; NOVRIYANDI HANIF; FRETS J. RIEUWPASSA; MARGARET HILL; TILL F. SCHÄBERLE (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Balansa W, Riyanti, Patras MA, Balansa KH, Hanif N, Rieuwpassa FJ, Hill M, Schäberle TF. 2025. Harnessing the metabolites from the marine sponge Melophlus sarasinorum for the discovery of eco-friendly antifoulants. Biodiversitas 26: 1590-1606. Marine biofouling remains an unresolved issue in both the maritime industry and the marine environment, demanding the discovery of new eco-friendly antifoulants. This study aimed to evaluate the antifouling potential of the marine sponge, Melophlus sarasinorum (Thiele, 1899), through metabolomic, computational, and field studies. Seven compounds were dereplicated as sarasinosides A1-A3, D, L, M, and M2 (1-7) from extracts of M. sarasinorum from Kawaluso and Mahumu Islands. Molecular docking showed robust binding affinities for 1-7 (-8.2 to -9.6 kcal/mol), rivaling acetylcholinesterase (AChE) inhibitors, synoxazolidinones A (8) and C (9), commercial antifoulants medetomidine/selektope® (12) and econea® (13) (-9.2, -9.3, -9.5, -9.3 kcal/mol, respectively) as well as the antifouling agents, seanin_211 (10) (-8.9 kcal/mol) and irgarol_1505 (11) (-5.5, -6.5 kcal/mol, respectively). The strong binding affinities of 1-7 suggest possible new allosteric interactions with AChE. The ANOVA test revealed a significant difference in biofouling growth (p<0.05) between nets pre-treated with 1:1, 1:2, or 1:3 sponge powder/epoxy mixture compared to other treatments, as confirmed by a post-hoc Duncan test. Notably, toxicity studies with EPI SuiteTM indicated that 1-7 had more eco-friendly toxicological parameters (i.e., low Log Kow, Log Koc, Biotransformation Half-life, and water solubility) compared to AChE inhibitors and commercial antifouling agents (p<0.05). Our results demonstrate the antifouling activity of sarasinosides (1-7), providing insight into the design of novel, eco-friendly antifoulants that warrant further investigation into their mode of action and optimization.